In defense of religious moderation - Egginton, William, 1969- (Columbia University Press, 2011)
In his latest book, William Egginton laments the current debate over religion in America, in which religious fundamentalists have set the tone of political discourse and prominent atheists treat religious belief as the root of all evil. Neither of these positions, he argues, adequately represents the attitudes of a majority of Americans, who, while identifying as Christians, Jews, and Muslims, do not find fault with those who support different faiths and philosophies. In fact, Egginton goes so far as to question whether fundamentalists and atheists truly oppose each other, united as they are in their commitment to a "code of codes."